Cultural politics and education - Apple, Michael W. (Open University Press, 1996)
Education, identity, and cheap French fries. The politics of official knowledge: does a national curriculum make sense? Becoming right: education and the formation of conservative movements with Anita Oliver. American realities. Conclusion.